Posttraumatic Growth (PTG) Among Parents of Children With Special Needs. Issue 1 (2nd January 2022) - Laufer, Avital; Isman, Esther
Abstract: The study investigated posttraumatic growth (PTG) among parents of children with special needs, and its relation with parental stress and parental mental health. The sample comprised 257 urban Israeli parents of children with various special needs. PTG was reported by 63% of the parents. The greatest change reported was in life appreciation (74%) followed by personal strength (69%). The lowest was in spiritual change (39%). Results indicate that stress, stemming from being a parent of a child with special needs, is a contributor to the parent's overall PTG.